Using an arithmetic sequence, the formula for the nth term is given by:
[tex]a_n = -2 - 2n, n \geq 1[/tex]
-------------------------------
[tex]a_n = a_1 + (n-1)d[/tex]
In the recursive sequence, we have that:
[tex]f(0) = -4[/tex]
[tex]f(n) = f(n-1) - 2[/tex]
Then
[tex]f(1) = f(0) - 2 = -4 - 2 = -6[/tex]
[tex]f(2) = f(1) - 2 = -6 - 2 = -8[/tex]
And so on...
The sequence is: {-4, -6, -8,...}
Which is an arithmetic sequence with [tex]a_1 = -4[/tex] and [tex]d = -2[/tex], thus, the definition for the nth term is:
[tex]a_n = a_1 + (n-1)d[/tex]
[tex]a_n = -4 - 2(n-1)[/tex]
[tex]a_n = -4 - 2n + 2[/tex]
[tex]a_n = -2 - 2n, n \geq 1[/tex]
A similar problem is given at https://brainly.com/question/23901992